PERUBAHAN KANDUNGAN BETA KAROTEN, TOTAL ASAM, DAN SIFAT SENSORIK YOGHURT LABU KUNING BERDASARKAN LAMA SIMPAN DAN PENCAHAYAAN - Tri Ayu Yulianawatia; Joko Teguh Isworo (Jurnal Pangan dan Gizi, 2012)
Pumpkin (Cucurbita moschata) is one of the local foodstuffs which have good nutritional value for the human body. Diversification it into functional food pumpkin is necessary, that is by processing pumpkins into yogurt. The research purposes of this study are to determine the effect of length storage and lighting to the content of beta carotene, total acid and sensory properties of pumpkin yoghurt. The research conducted a completely randomized design (CRD). The results analysis of beta-carotenes content of fresh pumpkins of 0.82 mg/100 g after processed into yoghurt by storage time and lighting at the highest levels of beta-carotene by 0.071 mg/100 g on 2nd day in darkness packaging, while the lowest levels of beta-carotene of 0.050 mg/100 g on 4th in darkness packaging. The highest total acid found in pumpkins yogurt in light packaging on 10th day in the amount of 1.047%, whereas lowest total acid present in yoghurt pumpkins in darkness packaging on 2nd day is 0.981%. Lighting treatment and storage time had not significant on changes in the levels of beta-carotene and total acid. The level of preferences indicate that storage time the 6th day of the desirability of consistency, flavor, aroma, and color. Keywords: yogurt, pumpkin, length storage, lighting, beta carotene, acid total, sensory properties.